The Effect of Tax Avoidance and Leverage on Company Value (Case Study of State-Owned Enterprises Listed on the Indonesian Stock Exchange (BEI) 2020-2024) - Ranita Waliyyuna; Rizky Pratama Putra (Green Publisher Indonesia, 2026)
This study examines the effect of tax avoidance and leverage on firm value in Badan Usaha Milik Negara (BUMN) listed on the Indonesia Stock Exchange during 2021–2024. A quantitative causal approach was employed with 15 BUMN selected through purposive sampling. Secondary data were obtained from annual financial statements. Tax avoidance was measured using the Cash Effective Tax Rate (CETR), leverage using the Debt to Equity Ratio (DER), and firm value using Tobin’s Q. Panel data regression with the Fixed Effect Model (FEM) was applied using EViews 12. The results show that tax avoidance and leverage have no significant effect on firm value, either partially or simultaneously. The results show that tax avoidance and leverage have no significant effect on firm value, either partially or simultaneously. This indicates that BUMN firm value is influenced by factors beyond tax policy and capital structure.